Nutritional responses to different diet quality in the subterranean rodent Ctenomys talarum (tuco-tucos) - Martino, Natalia Silvana (2007)
Nutritional response to different diet quality was examined in the subterranean rodent Ctenomys talarum (tuco-tuco). Animals maintained in captive conditions were fed with three plant species that differed in their fibre content. Tuco-tucos showed the ability to perform adjusts in short time lapse in response to diet quality; food ingestion, egestion and feces ingestion changed in animals under different plant species diets. Time budget, mainly time devoted to feeding and activity accompanied such changes. Coprophagy was practiced along the day and night following the arrhythmic activity pattern found for this species. Feces reingestion was not associated to resting. Furthermore, it was observed during fresh food ingestion, being pellets chewed. Soft and hard feces differed in morphological and nutritional characteristics